The role of sustainability in attracting talent to Small & Medium Enterprises (Singapore) - Gn, Kenneth Jong Bin (2025)
This dissertation examines the role of sustainability in attracting talent to Small and Medium Enterprises (SMEs) in Singapore. As sustainability gains importance for businesses globally, job seekers, especially from younger generations, are placing more emphasis on a company's environmental and social impact when choosing their careers. The research aims to explore how SMEs in Singapore can leverage sustainability efforts as a key differentiator in the highly competitive talent market, where they often face challenges in competing with bigger companies for top talent. A quantitative survey of adult workers in Singapore will be conducted and analysed to determine the importance of sustainability in shaping sentiments about an employer’s attractiveness. The findings aim to investigate the importance of sustainability toward talent attraction but also in employee engagement. Many prospective employees, particularly Millennials and Generation Z, have a higher propensity to join companies that align with their values, prioritizing purpose, ethical business practices, and environmental responsibility alongside traditional benefits. However, beyond sustainability as a key factor, the research will verify if there are other contributing factors influencing perception, sentiments, reputation and job appeal. This dissertation will conclude by providing recommendations for SMEs on integrating sustainability and other aspects into their business strategies and employer branding, so as to enhance their appeal to talents, and enhance their competitiveness and overall success in Singapore's dynamic economic landscape.